Eureka! An Early Career Designer's Insight on the Design Process - Lunga, Makhosazana L.; Howard, Craig D. (International Journal of Designs for Learning, 2022)
This design case presents an early career designer’s reflection on the design and design narrative from an asynchronous video tutorial, reflecting on the unexpected obstacles of the process and unintended consequences of certain design decisions. The first author designed a tutorial for a non-academic department of a large southeastern university. The first author was an early career instructional designer at the time of this design. She shares insights that she gained through this design process, reflecting on developing communication strategies for working with the client and other stakeholders, as well as the critical moments where she might have avoided design failures. The second author mentored her and supported the design case’s development. He has included reflection notes in the article in key locations where common challenges to writing the case appeared. This design case details how assumptions and infrequent communication, or communication that lacked vital details, impacted the design process. It offers readers pivotal discoveries that figured prominently in the final design and compelled the designer to reflect on how the design came to be as it was. The case aims to share the precedent embodied in the design (Howard et al., 2012). This case is presented not to generalize about all cases but rather to offer readers the opportunity to find their own utility in the narrative and reflections. We hope that sharing this experience of reflecting on design inspires creativity in overcoming challenges to communication and collaboration.